Genetic Algorithm Application in Asymmetrical 9-Level Inverter - Rachid Taleb; M’hamed Helaimi; Djilali Benyoucef; Zinelaabidine Boudjema (Institute of Advanced Engineering and Science, 2016)
Selective harmonic elimination (SHE) has been a widely researched alternative to traditional PWM techniques. This paper presents the selective harmonic elimination of a uniform step asymmetrical multilevel inverter (USAMI) using genetic algorithm (GA) which eliminates specified higher order harmonics while maintaining the required fundamental voltage. This technique can be applied to USAMI with any number of levels. As an example, in this paper a 9-level USAMI is considered and the optimum switching angles are calculated to eliminate the 5th, 7th and 11th harmonics.